Inscriptions on the floor of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
Interestingly, the floor of the mukhamandapa (front porch) of the Ghateshwar Temple is engraved with numerous inscriptions. On paleographic grounds, it can be observed that the inscriptions on the floor are heterogeneous and belong to different periods. Their lack of sequence or order further suggests that they belong to different time periods.